A Survey on Knowledge about Oxidative Stress and Inflammatory Disease among Dental Students - S.M.Sowbaraniya1 , Anitha Roy2 , N.P.Muralidharan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oxidative stress is caused by an imbalance between production and accumulation of oxygen reactive speciesin cells and tissues which can lead to various neuronal degenerative diseases and also oral diseases such asperiodontitis and dental caries. Long term inflammation can lead to an inflammatory disease which is alsodue to impairment of the immune system in healthy tissue. In oral cavity it may cause conditions such asperiodontitis, gingivitis.The aim of the study was to assess the knowledge and awareness regarding oxidativestress and inflammatory disease among dental students . A survey was conducted among 100 dental studentsin a private dental college. The questionnaire was circulated through google forms. Ten questions relatedto oxidative stress and inflammatory disease were included in the study and the responses were collectedand analysed using SPSS.Chi-Square test was carried out and p <0.05 was considered as significant. It wasobserved that 80% of students were aware about increase in oxidative stress and 60% of students were awareof oral disease such as periodontitis which helps in treatment plan of the patients .85% of students thinks thatstress was also one of the reasons for increasing oxidative stress.80% of students were with the opinion thatincreased oxidative stress increase the chance of getting various inflammatory disease.50% of students wereaware that using antioxidant supplements increase the survival rate of patient and showed better therapeuticresponse.It was observed that students were aware of clinical symptoms and the effects of oxidative stress inoral health and various reasons for causing inflammatory disease. However, still more knowledge regardingthis will help in early diagnosing of disease caused by oxidative stress and inflammatory disease.